Indelible Footprints in Macau - Miu Bing Cheng, Christina (2022)
This work is financed by national funds through FCT - Foundation for Science and Technology, I.P, in the scope of the projects UIDB/04311/2020 and UIDP/04311/2020. | Este trabalho é financiado por fundos nacionais através da FCT – Fundação para a Ciência e a Tecnologia, I.P., no âmbito dos projetos UIDB/04311/2020 e UIDP/04311/2020.